153k views
4 votes
Please help! Thanks

Please help! Thanks-example-1

1 Answer

6 votes

Answer:

x = +-sqrt(3) and they are the actual solutions

Explanation:

x^2/ (2x-6) = 9/(6x-18)

get a common denominator of 6x-18

x^2/ (2x-6) * 3/3 = 9/(6x-18)

3x^2/ (6x-18) = 9/(6x-18)

since the denominators are the same, the numerators must be the same

3x^2 = 9

divide by 3 on each side

x^2 = 3

take the square root of each side

sqrt(x^2) = +-sqrt(3)

x = +-sqrt(3)



User Bart De Boeck
by
5.5k points